A cis‐eQTL of HLA‐DRB1 and a frameshift mutation of MICA contribute to the pattern of association of HLA alleles with cervical cancer. (12th February 2014) - Chen, Dan; Gyllensten, Ulf
Abstract The association of classic human leukocyte antigen (HLA) alleles with risk of cervical cancer has been extensively studied, and a protective effect has consistently been found for DRB1*1301, DQA1*0103, and/or DQB1*0603 (these three alleles are in perfect linkage disequilibrium [LD] and often occur on the same haplotype in Europeans), while reports have differed widely with respect to the effect of HLA‐B*07, DRB1*1501, and/or DQB1*0602 (the last two alleles are also in perfect LD in Europeans). It is not clear whether the reported HLA alleles are responsible for the differences in cervical cancer susceptibility, or if functional variants at other locations within the major histocompatibility complex (MHC) region may explain the effect. In order to assess the relative contribution of both classic HLA alleles and single‐nucleotide polymorphisms (SNPs) within the MHC region to cervical cancer susceptibility, we have imputed classic HLA alleles in 1034 cervical cancer patients and 3948 controls in a Swedish population for an integrated analysis. We found that the protective haplotype DRB1*1301‐DQA1*0103‐DQB1*0603 has a direct effect on cervical cancer and always occurs together with the C allele of a HLA‐DRB1 cis‐eQTL (rs9272143), which increases the expression of HLA‐DRB1. The haplotype rs9272143C‐DRB1*1301‐DQA1*0103‐DQB1*0603 conferred the strongest protection against cervical cancer (odds ratio [OR] = 0.41, 95% confidence interval [CI] = 0.32–0.52, P = 6.2 × 10−13). On the other hand, the associations with HLA‐B*0702 and DRB1*1501‐DQB1*0602 are attributable to the joint effects of both the HLA‐DRB1 cis‐eQTL (rs9272143) and a frameshift mutation (G inserion of rs67841474, also known as A5.1) of the MHC class I polypeptide‐related sequence A gene (MICA). Variation in LD between the classic HLA loci, rs9272143 and rs67841474 between populations may explain the different associations of HLA‐B*07 and DRB1*1501‐DQB1*0602 with cervical cancer between studies. The mechanism suggested may also explain similar inconsistent results for other HLA‐associated diseases.